Methodological proposal to analyze land use and land cover changes: the case of Santa Catarina state in Brazil from 2000 to 2010 - Souza, Juliana (2021)
The aim of this paper is to examine land use and land cover changes and to relate it to the potential driving forces observed in the state of Santa Catarina, Brazil, during the period from 2000 to 2010. The methodology consists of identifying trends in land use and land cover changes; indicating possible explanatory factors by means of Principal Component Factor Analysis and elaborating a final typology, based on Cluster Analysis. Results point to the considerable expansion and increased intensity of agricultural activity as well as silviculture throughout the state and the loss of native vegetation, suggesting the need for protective actions and land use and cover regulations, particularly from an environmental perspective, to frame the development of intensive and mechanized agricultural activity.